2021
DOI: 10.37148/comphijournal.v2i1.33
|View full text |Cite
|
Sign up to set email alerts
|

Studi Faktor Resiko Preeklamsia terhadap Kejadian Berat Badan Lahir Rendah (BBLR)

Abstract: Introduction: The number of infant mortality rates (IMR) in Indonesia still receives serious attention in health. The risk of increased infant mortality rates was found in infants with low birth weight. This happened because the baby will have growth and development problems, so they are more at risk of getting the disease. One of the causes of low-birth-weight babies is a history of preeclampsia during pregnancy. Objective: This study aims to determine the risk of preeclampsia on the increase in the incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(13 reference statements)
2
1
0
Order By: Relevance
“…Research by Azzizah et al [8] reveals that mothers with preeclampsia have a 2.391 times higher risk of giving birth to LBW babies compared to mothers without preeclampsia. This finding aligns with the results of the study by Hanif et al [11], which showed that mothers with severe preeclampsia had 40 cases of LBW, while those without preeclampsia had 45 cases of LBW. Aryana et al's research [10] also supports these findings, confirming that a significant factor influencing LBW is maternal blood pressure.…”
Section: Hanif Et Al [11]supporting
confidence: 92%
“…Research by Azzizah et al [8] reveals that mothers with preeclampsia have a 2.391 times higher risk of giving birth to LBW babies compared to mothers without preeclampsia. This finding aligns with the results of the study by Hanif et al [11], which showed that mothers with severe preeclampsia had 40 cases of LBW, while those without preeclampsia had 45 cases of LBW. Aryana et al's research [10] also supports these findings, confirming that a significant factor influencing LBW is maternal blood pressure.…”
Section: Hanif Et Al [11]supporting
confidence: 92%
“…And mothers who have preeclampsia have 1.85 times more likely to give birth to LBW compared to mothers who do not have preeclampsia. This study is similar to the research conducted by [13] with the title "Study of Preeclampsia Risk Factors on Low Birth Weight (LBW)", which states that there is a relationship between preeclampsia and LBW incidence (p = 0.000; r = 0.46). In addition, the risk of the incidence of LBW infants in severe preeclampsia was higher than with mild preeclampsia (OR=11.5).…”
Section: Literature Reviewsupporting
confidence: 82%
“…Based on the findings obtained in the study [13] showed that the percentage of mothers aged 35 years who gave birth to LBW babies (40.9%) was greater than those aged 35 years who gave birth to babies with normal weight (20.5 %). This study is in line with research conducted [1] Pregnancy at the age of <20/>35 years causes a lack of adequate nutritional intake for fetal growth so that it can cause babies with low birth weight this is because at the age of <20 years the female reproductive organs immature and immature as well as psychologically pregnant women so that it has an impact on the less than optimal growth of the fetus in the mother's womb.…”
Section: Relationship Between Early Pregnancy and Lbwmentioning
confidence: 87%